Echocardiographic Predictors of All-Cause Mortality in Patients with Hypertrophic Cardiomyopathy following Pacemaker Implantation - Nixiao Zhang; Wei Hua; Xiaoping Li; Yiran Hu; Hongxia Niu; Chi Cai; Min Gu; Xuhua Chen; Shu Zhang (Cardiology Research and Practice)
Objectives. To examine the association between the echocardiographic parameters measured as left atrial diameter (LAD) and left ventricular end-diastolic diameter (LVEDD) and long-term risk of all-cause mortality in adults with hypertrophic cardiomyopathy (HCM) following pacemaker implantation. Methods. A total of 94 adult patients with HCM who underwent pacemaker implantation from November 2002 to June 2013 in our Arrhythmia Center for symptomatic bradycardia and did not receive an implantable cardiac defibrillator (ICD) or cardiac resynchronization therapy (CRT) during follow-up were retrospectively extracted. Results. After careful examination of the medical records, we retrospectively evaluated the clinical characteristics of 74 patients with LAD records (58.1 ± 14.9 years) and 76 patients with LVEDD records (57.6 ± 15.2 years). Based on the receiver-operating characteristic (ROC) curve, the values of LAD = 44 mm and LVEDD = 43 mm were identified to predict the all-cause mortality. In the Kaplan–Meier survival, LAD ≥44 mm and LVEDD ≥43 mm were both significantly associated with all-cause mortality (log-rank test P<0.05). Cox regression analysis indicated that LAD ≥44 mm (HR 3.580; 95% CI = 1.055–12.148; P=0.041) was an independent predictor of all-cause mortality, while LVEDD ≥43 mm was not significantly associated with all-cause mortality. LVOTO was also significantly associated with all-cause mortality (HR = 0.166; 95% CI = 0.036–0.771; P=0.022). Conclusions. In HCM patients with pacemaker implantation, LAD ≥44 mm was an independent predictor of all-cause mortality.